Evaluasi Implementasi Sistem Informasi Rumah Sakit Gigi Dan Mulut Universitas Muhammadiyah Yogyakarta Ditinjau Dari Technology Acceptance Model - Taufiq Aribowo (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2019)
Dental Hospital of Muhammadiyah University of Yogyakarta is a hospital that serves the public as well as a place to practice for dentistry students of Muhammadiyah University of Yogyakarta. RSGM uses an integrated hospital information system and is used by hospital staff, lecturers and students. This study aims to obtain information about the use of information systems as well as test and analyze the acceptance of technology by using the Technology Acceptance Model (TAM), based on previous research using this theory. A survey methodology was used to collect data from 144 respondents. The sensitivity of the questionnaire was achieved by adopting a five-point Likert scale. This study uses SPSS version 20 to obtain frequency distribution, and using SmartPLS software version 3.0 which gives result of causal relation between variables that influence each other. The results showed that the Perceived Ease of Use (PEoU) variable had a positive effect of 0.23 on Behavioral Intentions (BI). The magnitude of the parameter coefficient for Perceived Usefulness (PU) variable against BI has a positive influence of 0.414. PEOU has a positive value against PU of 0.431 and is considered significant. The coefficient parameter Perceived Importance of Documentation (PIoD) to PU value is 0.082, it can be stated that the effect of variable is not too significant. PU is significantly affected by Perceived of IT Utilization (PIoITU) of 0.322. PEOU is significantly affected by Perceived Importance of Standardization (PIoS) of 0.401. The variable of PU to BI has a positive and significant influence of 0.414. While the magnitude of the parameter coefficients for the Perceived of Data Security (PUoDS) variable against PU has a positive influence of 0.082 which is not significantly influential.